2017
DOI: 10.1177/1071100717730328
|View full text |Cite
|
Sign up to set email alerts
|

A Radiographic Dye Method for Intraoperative Evaluation of Syndesmotic Injuries

Abstract: III, comparative series.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…In a study, preoperative CT in the diagnosis of the syndesmosis was compared with the Chertsey test (a radiographic dye method for intraoperative evaluation of syndesmotic injuries), which is one of the intraoperative tests for diagnosing syndesmotic injuries [ 24 ]. The Chertsey test was found positive in 13 (33.3%) of 39 patients diagnosed syndesmotic injury in preoperative CT, which was found valuable in diagnosing syndesmosis.…”
Section: Discussionmentioning
confidence: 99%
“…In a study, preoperative CT in the diagnosis of the syndesmosis was compared with the Chertsey test (a radiographic dye method for intraoperative evaluation of syndesmotic injuries), which is one of the intraoperative tests for diagnosing syndesmotic injuries [ 24 ]. The Chertsey test was found positive in 13 (33.3%) of 39 patients diagnosed syndesmotic injury in preoperative CT, which was found valuable in diagnosing syndesmosis.…”
Section: Discussionmentioning
confidence: 99%
“…[ 13 ] Pepe et al . [ 27 ] in a study comparing the diagnostic value of preoperative CT scan and intraoperative Chertsey test stated that the dye injection test was positive in 13 out of 39 cases (33.3%) of ankle fractures. In their study, patients categorized as Chertsey positive demonstrated a noteworthy increment in the width and volume of the syndesmosis in comparison to the control group which is consistent with the present study results.…”
Section: Discussionmentioning
confidence: 99%
“…They generally concluded that the Chertsey test is a decisive and advantageous test that can easily be performed during surgery to diagnose syndesmosis injuries. [ 27 ] Yeung et al . in a study of ankle fractures revealed that the mean ATFD, MTFD, PTFD, and MAXTFD in Chertsey positive group were 4.9 ± 3.7 mm, 5.3 ± 2.4 mm, 5.3 ± 1.8 mm, and 7.2 ± 2.96 mm, respectively, and in the Chertsey negative group were 4.2 ± 4.2 mm, 5.1 ± 3.1 mm, 5.0 ± 1.7 mm, and 6.3 ± 3.7 mm, respectively.…”
Section: Discussionmentioning
confidence: 99%